2006
DOI: 10.1002/jclp.20321
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine approaches to pain management

Abstract: This article argues for and illustrates incorporating complementary and alternative medicine (CAM) interventions into pain treatment plans. Two CAM treatments, cranial electrotherapy stimulation (CES) and self-hypnosis training, are offered in a multidisciplinary pain treatment program. Because these interventions focus on pain relief, they may be of particular interest to patients who have chronic pain who begin treatment with a primary interest in pain reduction. Two cases that illustrate the clinical applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Efficacy and safety of several CAM techniques have been addressed by several investigators. 5,[36][37][38][39][40][41] Many curative ingredients are found in medicinal plants that have been proven to be valuable as primary or supplemental therapies when carefully applied. 42 Herbal therapy and prayers were the most commonly used CAM among the respondents in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy and safety of several CAM techniques have been addressed by several investigators. 5,[36][37][38][39][40][41] Many curative ingredients are found in medicinal plants that have been proven to be valuable as primary or supplemental therapies when carefully applied. 42 Herbal therapy and prayers were the most commonly used CAM among the respondents in our study.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] Complementary therapies are also used in the treatment of TTH. [27][28][29][30][31] Chiropractic spinal manipulation (CSM) is one of these. Systematic reviews by Vernon et al, 32 Bronfort et al, 33,34 Fernandez de las Penas et al, 35 and Lenssinck et al 36 identified two trials of CSM for TTH, one of which employed amitriptyline as the comparator, demonstrating benefit equal to that of amitriptyline after six weeks of spinal manipulation 37 and the other demonstrating benefits no greater than soft tissue massage.…”
mentioning
confidence: 99%
“…In neurofeedback electroencephalographic signals control the feedback signal. Neurofeedback has been used to treat several neuropsychiatric disorders including depression [16][17] , post-traumatic stress disorder 18 , traumatic brain injury [19][20][21] and chronic pain 22 . In these treatments the feedback signal to the patient is usually constructed from the spectral properties of the signal, for example alpha asymmetry.…”
Section: Discussionmentioning
confidence: 99%